2022
DOI: 10.3390/ma16010013
|View full text |Cite
|
Sign up to set email alerts
|

Copper Iodide on Spacer Fabrics as Textile Thermoelectric Device for Energy Generation

Abstract: The integration of electronic functionalities into textiles for use as wearable sensors, energy harvesters, or coolers has become increasingly important in recent years. A special focus is on efficient thermoelectric materials. Copper iodide as a p-type thermoelectrically active, nontoxic material is attractive for energy harvesting and energy generation because of its transparency and possible high-power factor. The deposition of CuI on polyester spacer fabrics by wet chemical processes represents a great pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…(5) Compression test speeds do not seem to have a significant impact on the compression results of multi-layered spacer fabrics. (6) The overlaid orders of different types of spacer fabrics will affect their compression performance, especially for their modulus. It is ideal to overlay the fabric with a large modulus on top, followed by the fabric with a small modulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) Compression test speeds do not seem to have a significant impact on the compression results of multi-layered spacer fabrics. (6) The overlaid orders of different types of spacer fabrics will affect their compression performance, especially for their modulus. It is ideal to overlay the fabric with a large modulus on top, followed by the fabric with a small modulus.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is widely used in various industries for good air permeability, moisture permeability, pressure relief and impact resistance. [2][3][4][5][6] Currently, the thickness of spacer fabrics generally ranges from 2 to 25 mm. 7 The weaving process of large-gauge fabrics is still immature, 8 and there are problems such as low weaving efficiency and high requirements for mechanical parts.…”
mentioning
confidence: 99%
“…Aside of sound waves, also the transport of heat is mediated via phonons. Here, low thermal conductivity may be used for thermal barriers [5] or as well in in thermoelectric applications [6,7]. These thermal transport properties though, are directly linked to phonon anharmonicities.…”
Section: Introductionmentioning
confidence: 99%
“…We will show this exemplarily on copper iodide (CuI), which has at room temperature (RT) a zinc blende crystal structure. It is known for its strong anharmonic properties [5,9,10], which reflects in CuI's coefficient of thermal conduction, which is as low as 0.5 W m −1 K −1 and hence the dimensionless figure of merit ZT is about 0.25 [6,7,11]. These are promising values for device applications, especially for transparent electronics due to its wide bandgap of 3.1 eV [12] and a hole mobility of up to 43 cm 2 V −1 s −1 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most TC TE materials (zinc oxide, indium oxide, indium tin oxide, and strontium titanium oxide) exhibit n -type TE properties. Consequently, it is essential to develop air-stable and highly conductive p -type TC TE materials, as n -type counterparts, for realizing efficiently integrated thermoelectric generators (TEGs) with high power outputs. Recently, copper iodide (CuI) has been touted as a promising p -type TC TE material because it demonstrates several advantages, such as facile control of its electronic and phonon transport properties, and CuI is easily accessible through many synthetic methods. The high intrinsic electrical conductivity of CuI results from copper vacancies with high hole mobility and this can be further improved by controlling the iodine content through engineered doping. Furthermore, as a heavy element, iodine is favorable for TE performance improvements because it can reduce the lattice thermal conductivity. Polycrystalline CuI has been prepared using various physical or chemical deposition methods, such as sputtering, pulsed laser deposition, thermal evaporation, and solid, and vapor iodization. Although the best of these studies reported a relatively high electrical conductivity of near 150 S·cm –1 with a zT value near 0.21 at room temperature, the synthetic process required expensive equipment in large vacuum facilities to obtain the necessary high processing temperatures and execute the sophisticated vacuum-phase process .…”
mentioning
confidence: 99%